Study on effectiveness of communication amongst members at department of orthopedics surgery unit 3 using smartphone and mobile WhatsApp - Choudhari, Pradeep (International Surgery Journal, 2016)
Background:The objective of this study was to assess the effectiveness of smartphone and its WhatsApp application as a communication method amongst the members of department of orthopedic surgery unit 3 at SAIMS. Methods:From January 2013 onwards, the authors used smart phones and its WhatsApp application as a communication method amongst their team for various aspects of patient management and as a tool for academic endorsements. Results: During the period of this study, there were 95 incidences regarding patient management, which were handled, in a timely fashion by using this application. In addition opinion of residents in the unit was sought regarding the effectiveness of this method of communication. Overall majority of residents were satisfied with this mode of communication. Conclusion:This new method of communication is an effective method for clinical and academic endorsements. The method is cheap and quick and easy to operate.